Determination of Motorized Vehicle Tax Compliance in Terms of Awareness, PKB-BBNKB Optimization, and Public Service Accountability - Khusnul Khotimah; Muzayyanah; Itat Tatmimah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of taxpayer awareness, the PKB-BBNKB revenue-sharing policy (opsen), and public service accountability on motor vehicle taxpayer compliance in the jurisdiction of the Regional Revenue Management of Cirebon Regency I Sumber. The research adopts a quantitative approach using a survey method with a sample of 100 respondents selected through purposive sampling. Data are collected via questionnaires and analyzed using multiple linear regression with the help of SPSS 25.0 software. The results indicate that taxpayer awareness has a positive and significant effect on motor vehicle taxpayer compliance, suggesting that better understanding and concern about tax obligations increase the likelihood of compliance. The implementation of the PKB-BBNKB opsen policy also shows a positive and significant effect, reflecting that fiscal decentralization through revenue-sharing encourages local governments to improve tax collection systems and services, which in turn boosts taxpayer motivation. Furthermore, Additionally, public service accountability shows no significant impact. This insignificance may be due to the public's perception that public services are administrative and do not directly affect their decisions to comply with tax payments. The simultaneous test (F-test) confirms that the three independent variables collectively have a significant impact on taxpayer compliance.